Dietary administration with hydrolyzed silk sericin improves the intestinal health of diabetic rats - Zhou, Wenlin; Weng, Yujie; Liu, Qian; Wang, Chonglong; Zhang, Yu-Qing; Zhang, Xing; Ye, Aihong (Frontiers in Microbiology, 2023)
Type II diabetes (T2D) is a global epidemic disease with an increased incidence and prevalence. Gut microbiota plays an important role in controlling T2D development. Dietary administration of prebiotics, probiotics, and drugs, including metformin, showed the regulatory impact on the change of gut microbiota, which is associated with the improvement of glucose tolerance. In this study, silk sericin was manufactured into hydrolyzed sericin peptide (HSP) powders as a dietary additive to investigate the effect on the gut microbiota of T2D model rats. The results indicated that the HSP-augmented dietary administration lowers the fast glucose level of diabetic rats, and HSP augmentation induces a change in the gut microbiota composition of T2D model rats toward the normal rats. Some key taxa, including Lactobacillus gasseri, were suggested to be involved in controlling T2D development. This finding provides new insight into developing sericin as functional food or therapeutic prebiotics against T2D in clinical practice.